S5-2: Shifting the Perspective on Biological Movement Perception - Zsolt Palatinus (i-Perception, 2012)
Most efforts for understanding biological movement perception seem to agree in assuming a key role of some version of 2D projective geometry being the basis of either computation or invariant detection somewhere between the stimulus and perception. Recent studies invite considering alternatives. Beintemma and Lappe (2002 PNAS 99 5661–5663) constructed sequential walker displays in which points were assigned along limb segments at random position at each frame and still reported correct responses. In our study, point light displays were prepared from motion-capture data of humans performing everyday activities. Animations were rendered either from a fixed camera position or from a curvilinear trajectory around the target. Same mean response time in the two conditions suggests that information for making correct judgments remained accessible despite the superposition of camera movement induced changes on the projection. An alternative approach is offered, based on Gibson's (1986, Lawrence Erlbaum Associates) conceptualization of the ambient optic array, a continuous energy field in which perception-action systems are immersed. The registration of these energy distributions manifests in fractal, scale-invariant fluctuations of exploratory movements, suggesting that there may be subtle contributions of previously unrecognized fluctuations. Fractal fluctuations may serve as a modality-general substrate for detection of information for perception and even cognition (Dixon et al., 2012 Topics in Cognitive Science 4 51–62; Stephen & Hajnal, 2011 Attention, Perception, & Psychophysics 73 1302–1328) In this work, we consider the possibility that subtle fluctuations in seated posture and head sway moderate the effects of optical energy arrays upon the perceptual system.